2013
DOI: 10.2753/ree1540-496x4904s304
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Investment Strategy Matters: A Statistical Arbitrage Approach

Abstract: Abstract:In this study, we employ a statistical arbitrage approach to demonstrate that momentum investment strategy tend to work better in periods longer than six months, a result different from findings in past literature. Compared with standard parametric tests, the statistical arbitrage method produces more clearly that momentum strategies work only in longer formation and holding periods. Also they yield positive significant returns in an up market, but negative yet insignificant returns in a down market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first such study, which applies this approach for research focused on the behaviour of institutional investors. Barber et al (2007), Susai and Moriyasu (2007), Choe and Eom (2009), Menkhoff et al (2010), Chou and Wang (2011), Cici (2012), Kudryavtsev et al (2013), Sun et al (2013), Bodnaruk and Simonov (2014). Shapira and Venezia (2001), Garvey and Murphey (2004), Dhar and Zhu (2006), Rzeszutek (2016) Overconfidence Menkhoff et al (2006), De Venter and Michayluk (2008), Waweru et al (2008), Menkhoff (2010), Puetz and Ruenzi (2011), Eshraghi (2011) Our study provides addition to the scarce international literature on the fund managers' behaviour and their decision-making processes by focusing on the extensive analysis of their behavioural biases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, this is the first such study, which applies this approach for research focused on the behaviour of institutional investors. Barber et al (2007), Susai and Moriyasu (2007), Choe and Eom (2009), Menkhoff et al (2010), Chou and Wang (2011), Cici (2012), Kudryavtsev et al (2013), Sun et al (2013), Bodnaruk and Simonov (2014). Shapira and Venezia (2001), Garvey and Murphey (2004), Dhar and Zhu (2006), Rzeszutek (2016) Overconfidence Menkhoff et al (2006), De Venter and Michayluk (2008), Waweru et al (2008), Menkhoff (2010), Puetz and Ruenzi (2011), Eshraghi (2011) Our study provides addition to the scarce international literature on the fund managers' behaviour and their decision-making processes by focusing on the extensive analysis of their behavioural biases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Sun et al (2013) aimed to explain disposition effect with momentum behavior and overconfidence. When both individual and institutional investor behavior in up and down markets were examined, it was seen that the increase of institutional investor momentum returns in particularly up markets raised overconfidence and that the increased overconfidence weakened disposition effect.…”
Section: Behavioral Biases On Institutional Investorsmentioning
confidence: 99%
“…In down markets, institutional investors employed contrarian strategy and this strategy similarly increased returns and overconfidence therefore reducing disposition effect. Barber et al (2007) and Sun et al (2013) investigated disposition effect in the same market for different periods of time and they both concluded that the absence of disposition effect was related to overconfidence. Some research other than these mentioned studies has explored disposition effect but provided no evidence of its presence.…”
Section: Behavioral Biases On Institutional Investorsmentioning
confidence: 99%
See 2 more Smart Citations